Análisis in silico de lipocalinas de perro, gato, caballo, vaca, hámster y gallina. Posible efecto en el estudio de las enfermedades alérgicas - Andrés Sánchez; Ricardo Cardona; Jorge Sánchez (Revista Alergia México, 2016)
Background: Lipocalins seem to explain the cross-reactivity between some pets like cat and dog. However, little has been studied its role in other animals and its possible clinical impact in allergy diseases.